2022
DOI: 10.3389/fnut.2022.942805
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-assisted extraction of anti-inflammatory compounds from habanero chili pepper (Capsicum chinense) seeds

Abstract: Capsaicinoids are the main bioactive compounds extracted from chili pepper seeds (CPSs) but other bioactive compounds such as phenolic compounds may be found. Enzyme-assisted extraction (EAE) improves the extraction of bioactive compounds from fruits and seeds. The aim of this study was to establish the cellulase-assisted extraction conditions of capsaicinoids and phenolic compounds from Habanero CPSs (Capsicum chinense) and to evaluate the anti-inflammatory activity of the obtained extracts on murine macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(37 reference statements)
0
5
0
1
Order By: Relevance
“…At 180 min, TPC was like the one obtained at 90 min (34.20 and 36.01 mg/L). Similar nonlinear results were obtained by Cortés-Ferré et al for Habanero chili pepper seeds. For ferulic and salicylic acids, the maximum TPC was also reached at 90 min and no significant difference was observed in comparison to the control group.…”
Section: Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…At 180 min, TPC was like the one obtained at 90 min (34.20 and 36.01 mg/L). Similar nonlinear results were obtained by Cortés-Ferré et al for Habanero chili pepper seeds. For ferulic and salicylic acids, the maximum TPC was also reached at 90 min and no significant difference was observed in comparison to the control group.…”
Section: Results and Discussionmentioning
confidence: 95%
“…Cytotoxicity assay was performed using the methodology reported by Cortés-Ferré et al using CellTiter 96® Aqueous One Solution Cell Proliferation Assay Kit (Promega, Madison, WI, USA) following manufacturer’s instructions. Subsequently, 100 μL of cell culture was inoculated at a density of 1 x 10 4 cells per well into 96-well plates and incubated at 37 °C for 24 h. After incubation time, cells were pretreated with 50 μL of JPS extracts at 0.01% (v/v) for 24 h before adding 50 μL of growth media (for control wells) or 50 μL of 10 μg/mL lipopolysaccharides (LPS) from Salmonella enterica serotype typhimurium (Sigma-Aldrich, St. Lous, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellulase-assisted extraction in water at 40−45 °C for a period of 150 min was best suited at a concentration of 2500 and 250 U L −1 for maximum phenolic compounds and capsaicinoids yield, respectively, from "Habanero" seeds. 206 Five times more capsaicinoids and carotenoids were extracted in the cellulase-treated "escabeche chili" (C. baccatum) powder than the control while using an extraction solvent mixture of hexane, acetone, and ethanol. 207 Treatment of "Tabasco Pepper" with 1 mL kg −1 pectinase and cellulase each increased the extract yield by 17.5% and enhanced the spice and flavor of the pepper sauce.…”
Section: Enzymatic Extractionmentioning
confidence: 99%
“…Cortés-Ferré et al (2022) demonstrated that Enzyme Assisted Extraction (EAE) allowed the recovery of compounds with anti-in ammatory activity from CPS using water as solvent. Although signi cant differences were observed in the CPS extracts obtained at different times, temperature and cellulase concentration, no statistically signi cant correlation was found between capsaicinoids or total phenolic content (TPC) with the NO synthesis [11].…”
Section: Introductionmentioning
confidence: 99%